Resting of sorghum-soya biscuit dough: effect on dough and biscuit physicochemical properties and consumer acceptability of the baked biscuits - De Kock, Henrietta Letitia (University of Pretoria, 2020)
Dissertation (MSc (Food Science))--University of Pretoria,2020.